Intruder Detection System (IDS) evasion / Solahuddin Yusuf Fadhlullah, Mohamad Adha Mohamad Idin and Mohd Halim Mohd Noor - Fadhlullah, Solahuddin Yusuf; Mohamad Idin, Mohamad Adha; Mohd Noor, Mohd Halim (Universiti Teknologi MARA Pulau Pinang, 2011)
Intrusion Detection System (IDS)is a technology, be it a software or harware, that automatically scans events occuring in computer or network for signs of security problems.